2022
DOI: 10.1097/mjt.0000000000001486
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review of Pharmacological Management of Postacute Sequelae of Severe Acute Respiratory Syndrome Coronavirus 2 Infection in 2021

Abstract: Background: Postacute sequelae of severe acute respiratory syndrome coronavirus 2 infection (PASC), or long-COVID, are signs and symptoms that persist after the acute phase of Coronavirus disease 2019 infection has passed. PASC is newly recognized, and research is ongoing to answer questions about pathology, symptoms, diagnosis, and optimal treatment. Areas of Uncertainty: Use of pharmacologic treatment for symptoms of PASC is currently evolving. This scoping review aims to assess medical literature for any ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…The authors identified the terms such as “long COVID,” “post‐COVID‐19 syndrome (PCS),” post‐acute sequelae of COVID‐19 (PACS), and “SARS‐CoV‐2 post‐viral fatigue syndrome.” The authors also recommended a need for consensus on the definition of PCC. Another scoping review on medications for PCC condition has recently been published and identified 52 relevant studies [38], investigating therapies such as ivabradine, beta‐adrenoreceptor blockers, and local and systemic corticosteroids. However, half of the identified studies were still ongoing, and the vast majority of completed studies were nonexperimental (i.e., case reports/series, observational studies), providing limited evidence on the efficacy of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The authors identified the terms such as “long COVID,” “post‐COVID‐19 syndrome (PCS),” post‐acute sequelae of COVID‐19 (PACS), and “SARS‐CoV‐2 post‐viral fatigue syndrome.” The authors also recommended a need for consensus on the definition of PCC. Another scoping review on medications for PCC condition has recently been published and identified 52 relevant studies [38], investigating therapies such as ivabradine, beta‐adrenoreceptor blockers, and local and systemic corticosteroids. However, half of the identified studies were still ongoing, and the vast majority of completed studies were nonexperimental (i.e., case reports/series, observational studies), providing limited evidence on the efficacy of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The immunomodulating therapy has been long in focus based on the inflammatory and autoimmune hypotheses in post-COVID-19 condition [36,78]. Although there is evidence of a beneficial effect of corticosteroids on symptoms and recovery during the acute phase in hospitalized patients [79][80][81], and specifically in patients with concomitant asthma [82][83][84], similar data on pharmacological treatment options for patients with post-COVID-19 condition is scarce [84]. The selection of an appropriate therapeutic approach to possible inflammatory and autoimmune disorders underlying post-COVID-19 condition is hampered by the fact that positive laboratory findings are unspecific or very limited.…”
Section: Managementmentioning
confidence: 99%
“…If the diagnosis is unclear, patients with symptoms of tachycardia, orthostasis, and blood pressure fluctuations should undergo autonomic testing such as tilt-table test, where available. Patients with confirmed POTS may benefit from a beta-blocker such as propranolol or ivabradine, a heart failure drug which can lower heart rate without reducing blood pressure [190]. Patients with orthostasis should maintain proper hydration, use compression stockings, abdominal binders, and participate in graded exercise programs on their back [191].…”
Section: Diagnosis and Treatmentmentioning
confidence: 99%
“…There are 26 ongoing studies for post-Covid syndromes [190]. However, due to the limited knowledge and lack of completed, successful studies for treatment in neuro-PASC, many doctors and patients have sought alternative routes for treatment.…”
Section: Experimental Therapiesmentioning
confidence: 99%